The Association Between Anxiety and Time to Community Release in a Sample of Incarcerated Women. (September 2022) - Pflugradt, Dawn M.; Allen, Bradley P.; Butler, Stephanie
Although the sociocultural factors impeding successful community re-integration for incarcerated women have been researched extensively, few studies have examined associated psychological influences. This study explored if there was a relationship between self-reported symptoms of anxiety and time to release from prison for a sample of incarcerated women. The results revealed that total self-reported symptoms of anxiety increased as time to release from prison decreased for all offenders regardless of the independent/predictor variable with the exception of age at index offense. The total scores of the Beck Anxiety Inventory (BAI) increased as the participants' age at time of index offenses decreased.